2021
DOI: 10.21873/invivo.12649
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Intraoperative Blood Loss on the Survival of Patients With Stage II/III Colorectal Cancer: A Multicenter Retrospective Study

Abstract: Background: Resection of the primary lesion with radical lymph node dissection is the most promising treatment avenue for patients with cancer. On the other hand, these procedures often induce excessive intraoperative blood loss (IBL) and require perioperative blood transfusion. The influence of IBL on the long-term postoperative outcomes of patients with digestive cancer is controversial. We investigated the impact of IBL on survival and recurrence after curative surgery in patients with colorectal cancer (CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…After browsing the titles and abstracts, 42 studies were left for full-text scanning. Finally, 7 studies (7,12,(17)(18)(19)(20)(21) were included in this study (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After browsing the titles and abstracts, 42 studies were left for full-text scanning. Finally, 7 studies (7,12,(17)(18)(19)(20)(21) were included in this study (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…A total of seven studies (7,12,(17)(18)(19)(20)(21) reported on OS and two studies (7,19) reported on DFS of patients with CRC who underwent radical CRC surgery. The random-effects model was used to calculate the HR values.…”
Section: Comparison Of Survival Outcomes Between the Larger And Small...mentioning
confidence: 99%
See 2 more Smart Citations
“…Data also correlated blood loss with short-term and long-term outcomes of CRC. The amount of intraoperative blood loss was associated with significant differences in the OS and DFS of patients with stage II/III CRC who received curative resection (13). Another study also found that the degree of blood loss during surgery for colon cancer was a factor that influences long-term survival (14).…”
Section: Discussionmentioning
confidence: 97%